2021
DOI: 10.1002/adhm.202101971
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalyst‐Mediated Chemodynamic Tumor Therapy

Abstract: Traditional tumor treatments, including chemotherapy, radiotherapy, photodynamic therapy, and photothermal therapy, are developed and used to treat different types of cancer. Recently, chemodynamic therapy (CDT) has been emerged as a novel cancer therapeutic strategy. CDT utilizes Fenton or Fenton-like reaction to generate highly cytotoxic hydroxyl radicals (•OH) from endogenous hydrogen peroxide (H 2 O 2 ) to kill cancer cells, which displays promising therapeutic potentials for tumor treatment. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 148 publications
0
83
0
Order By: Relevance
“…As a classic ROS-based anticancer modality, chemodynamic therapy (CDT) can catalyze endogenous H 2 O 2 into highly cytotoxic • OH via Fenton/Fenton-like reactions without relying on local oxygen content or external energy. [32][33][34] Previous research has demonstrated that Cu + -catalyzed Fenton-like reactions can proceed efficiently under both weakly acidic and neutral conditions, with a maximal reaction rate approximately 160 times higher than that of Fe 2+ . 35,36 Owing to the instability of Cu + , Cu 2+ is commonly utilized as a catalyst for CDT since it can be converted to Cu + by overexpressed GSH in cancer cells.…”
Section: •−mentioning
confidence: 99%
“…As a classic ROS-based anticancer modality, chemodynamic therapy (CDT) can catalyze endogenous H 2 O 2 into highly cytotoxic • OH via Fenton/Fenton-like reactions without relying on local oxygen content or external energy. [32][33][34] Previous research has demonstrated that Cu + -catalyzed Fenton-like reactions can proceed efficiently under both weakly acidic and neutral conditions, with a maximal reaction rate approximately 160 times higher than that of Fe 2+ . 35,36 Owing to the instability of Cu + , Cu 2+ is commonly utilized as a catalyst for CDT since it can be converted to Cu + by overexpressed GSH in cancer cells.…”
Section: •−mentioning
confidence: 99%
“…The achieved intracellular acidosis can not only cause cell damage, but also provide the suitable condition for iron (Fe)-based Fenton reaction. Under an acidic tumor microenvironment (TME), H 2 O 2 can be converted by Fe­(II) Fenton agents into toxic hydroxyl radical (·OH) to kill tumor cells. Chemodynamic therapy (CDT) is developed based on this reaction and attracts increasing attention, featuring high tumor specificity and minimal side effects. The efficacy of CDT can be promoted by pH regulation, substrate increasing, Fenton agent supplying, and photothermal effect. Besides, it is thrilling that the efficiency of CDT can be promoted by H 2 S, due to its function in suppressing the activity of catalase (CAT) and thus increasing the H 2 O 2 level .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these agents suffer from short circulation time in blood and poor tumor cell targeting ability, leading to a suboptimal therapeutic effect. Meanwhile, Mn and Cu ions always are more toxic to normal cells/tissues than Fe ions . Therefore, it is imperative to develop an Fe-based Fenton agent with more exposed active sites and effective tumor enrichment as a self-carrier to deliver CA IX inhibitors (CAI) and, thus, achieving self-amplified CDT and tumor metastasis inhibition via tumor microenvironment remodeling.…”
Section: Introductionmentioning
confidence: 99%